On Orthogonality Relations for Dual Discrete q-Ultraspherical Polynomials - Groza, V.A.; Kachuryk, I.I. (Symmetry, Integrability and Geometry: Methods and Applications, 2006)
The dual discrete q-ultraspherical polynomials Dn(s)(μ(x;s)|q) correspond to indeterminate moment problem and, therefore, have one-parameter family of extremal orthogonality relations. It is shown that special cases of dual discrete q-ultraspherical polynomials Dn(s)(μ(x;s)|q), when s = q⁻¹ and s = q, are directly connected with q⁻¹-Hermite polynomials. These connections are given in an explicit form. Using these relations, all extremal orthogonality relations for these special cases of polynomials Dn(s)(μ(x;s)|q) are found.